Patterns of Discordance Between Pretransplant Imaging Stage of Hepatocellular Carcinoma and Posttransplant Pathologic Stage: A Contemporary Appraisal of the Milan Criteria. Issue 4 (April 2018) - Ecker, Brett L.; Hoteit, Maarouf A.; Forde, Kimberly A.; Hsu, Christine C.; Reddy, K. Rajender; Furth, Emma E.; Siegelman, Evan S.; Habibollahi, Peiman; Ben-Josef, Edgar; Porrett, Paige M.; Abt, Peter L.; Shaked, Abraham; et al.
Abstract : Background: Patients with hepatocellular carcinoma (HCC) exceeding Milan criteria on explant pathology are at increased risk of recurrence and death. Discordance between contemporary magnetic resonance imaging (MRI) and explant pathology, and preoperative characteristics predictive of discordance are not well understood. Methods: Patients who underwent orthotopic liver transplantation for HCC after preoperative MRI were identified in a prospectively collected institutional database (January 2003 to December 2013). Patients were dichotomized to "within" or "outside" Milan criteria by both imaging and explant pathologic evaluation. Binary logistic regression and Kaplan-Meier methodology were used to identify independent predictors of imaging/pathologic discordance and its impact on posttransplant survival. Results: Of 318 patients with HCC meeting Milan criteria by MRI at the time of orthotopic liver transplantation, 248 (78.0%) remained within a pathological correlate of Milan criteria on explant examination. Understaging was associated with worse median recurrence-free survival (64.0 months vs 140.0 months, P = 0.002) and overall survival (96.0 months vs 143.0 months, P = 0.005), and did not vary between patients exceeding criteria due to tumor explant greater than 5 cm, more than 3 tumor foci, or a tumor greater than 3 cm in the setting of multifocality. Discordance was independently associated with an increasing serum alpha fetal protein level (odds ratio, 2.82; 95% confidence interval, 1.37-5.79; P = 0.005). Conclusions: Underestimating HCC burden before liver transplant remains frequent despite contemporary imaging technologies. Patients with an increasing alpha fetal protein before transplantation may benefit from more frequent testing or novel neoadjuvant therapies. Abstract : Understaging is the Achilles heel of liver transplantation for HCC. As might be expected, the authors show that understaging is associated with worse outcomes, but identify AFP as a potentially useful predictor of this higher risk group that could be targeted for interventions. Supplemental digital content is available in the text.